Biallelic Mismatch Repair Deficiency in an Adolescent Female. (25th July 2018) - Hildreth, Amber; Valasek, Mark A.; Thung, Irene; Savides, Thomas; Sivagnanam, Mamata; Ramamoorthy, Sonia; Huang, Sherry C.
Abstract : Constitutional (Biallelic) Mismatch Repair Deficiency is a rare autosomal recessive disorder characterized by numerous cancers presenting as early as the first decade of life. Biallelic germline variants in one of four mismatch repair genes ( MLH1, MSH2, MSH6, or PMS2 ) cause this devastating disease. Given the rarity of the syndrome, often-asymptomatic tumors, and overlap with neurofibromatosis-1, diagnosis is frequently unrecognized or delayed. We present a unique case of a 14-year-old female with minimal gastrointestinal symptoms diagnosed with invasive adenocarcinoma secondary to biallelic PMS2 variants.